Nutritional Aspects of Treatment in Epileptic Patients - SOLTANI, Danesh; GHAFFAR POUR, Majid; TAFAKHORI, Abbas; SARRAF, Payam; BITARAFAN, Sama (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Soltani D, Ghaffar pour M, Tafakhori A, Sarraf P, Bitarafan S. Nutritional Aspects of Treatment in Epileptic Patients. Iran J Child Neurol. Summer 2016; 10(3): 1-12. Abstract Epilepsy is a neurological disorder characterized by interruption of normal neuronal functions that is manifested by behavioral disorders, changing of awareness level, and presence of some sensory, autonomic and motor symptoms or signs. It is resulted from many different causes. Many antiepileptic drugs (AEDs) are considered to manage epileptic attacks. Some of them hange metabolism and absorption of many nutrients. Therefore, epileptic patients may be in higher risk of nutrient deficiency and its unwelcome effects. In the present paper, we intend to review the relationship between nutrition and epilepsy in two aspects. In one aspect we discuss the nutritional status in epileptic patients, the causes of nutritional deficiencies and the way of compensation of the nutrient deficiencies. It will guide these patients to have a healthy life. In another aspect we explain the role of some nutrients and specific diets in management of epileptic attacks. It can help to better control of epileptic attacks in these patients. References 1. Gragnani A, Müller BR, Oliveira AF, Ferreira LM. Burns and epilepsy–review and case report. Burns 2014;41:e15–e18. 2. Carlson C, Dugan P, Kirsch HE, Friedman D, Investigators E. Sex differences in seizure types and symptoms.EpilepsyBehav 2014; 41:103-8. 3. Speed D, O’Brien TJ, Palotie A, Shkura K, Marson AG, Balding DJ, et al. Describing the genetic architecture of epilepsy through heritability analysis. Brain 2014; 137:2680-9. 4. Poduri A, Sheidley BR, Shostak S, Ottman R. Genetic testing in the epilepsies developments and dilemmas. Nat Rev Neurol 2014; 10:293-9. 5. Malkan A, Beran RG. An appraisal of the new operational definition of epilepsy-Then and now. Epilepsy Behav 2014; 41:217-20. 6. Wong VC, Fung C, Kwong AK. SCN2A mutation in a Chinese boy with infantile spasm-response to Modified Atkins Diet. Brain Dev 2014; 37:729-732. 7. Rogawski MA. KCNQ2/KCNQ3 K. channels and the molecular pathogenesis of epilepsy: implications for therapy. Trends Neurosci 2000; 23:393-8. 8. Annegers JF, Hauser WA, Coan SP, Rocca WA. A population-based study of seizures after traumatic brain injuries. N Engl J Med 1998; 338:20-24. 9. Falconer Ma, Serafetinides Ea, Corsellis Jn. Etiology and pathogenesis of temporal lobe epilepsy. Arch Neurol 1964; 10:233-48. 10. Menon B, Shorvon SD. Ischaemic stroke in adults and epilepsy. Epilepsy Res 2009; 87:1-11. 11. Annegers J, Hauser W, Beghi E, Nicolosi A, Kurland L. The risk of unprovoked seizures after encephalitis and meningitis. Neurology 1988; 38:1407-10. 12. Matera G, Labate A, Quirino A, Lamberti AG, Borzì G, Barreca GS, et al. Chronic neuroborreliosis by B. garinii: an unusual case presenting with epilepsy and multifocal brain MRI lesions. New Microbiol 2014; 37:393-97. 13. Rajneesh KF, Binder DK. Tumor-associated epilepsy. Neurosurg Focus 2009; 27:E4. 14. Kovac S, Abramov AY, Walker MC. Energy depletion in seizures: Anaplerosis as a strategy for future therapies. Neuropharmacology 2013; 69:96-104. 15. Prasad C, Rupar T, Prasad AN. Pyruvate dehydrogenase deficiency and epilepsy. Brain Dev 2011; 33:856-65. 16. Seven M, Basaran SY, Cengiz M, Unal S, Yuksel A. Deficiency of selenium and zinc as a causative factor for idiopathic intractable epilepsy. Epilepsy Res 2013; 104:35-39. 17. Xiang J, Jiang Y. Regulation of Cu-Zn superoxide dismutase on SCN2A in SH-SY5Y cells as a potential therapy for temporal lobe epilepsy. Mol Med Rep 2014; 9:16-22. 18. Mintzer S, Skidmore CT, Sperling MR. B-Vitamin deficiency in patients treated with antiepileptic drugs. Epilepsy Behav 2012; 24:341-4. 19. Apeland T, Mansoor MA, Pentieva K, McNulty H, Strandjord RE. Fasting and post-methionine loading concentrations of homocysteine, vitamin B2, and vitamin B6 in patients on antiepileptic drugs. Clin Chem 2003;49:1005-8. 20. Brodie MJ, Mintzer S, Pack AM, Gidal BE, Vecht CJ, Schmidt D. Enzyme induction with antiepileptic drugs: cause forconcern? Epilepsia 2013; 54:11-27. 21. Miziak B, Blaszczyk B, Chroscinska-Krawczyk M, Danilkiewicz G, Jagiello-Wójtowicz E, Czuczwar SJ. The problem of osteoporosis in epileptic patients taking antiepileptic drugs. Expert Opin Drug Saf 2014; 13:1-12. 22. Gough H, Goggin T, Bissessar A, Baker M, Crowley M, Callaghan N. A comparative study of the relative influence of different anticonvulsant drugs, UV exposure and diet on vitamin D and calcium metabolism in outpatients with epilepsy. QJM 1986; 59:569-77. 23. Hahn TJ. 6 Drug-induced disorders of vitamin D and mineral metabolism. Clin Endocrinol Metab 1980; 9:107-29. 24. Roe DA. Diet and Drug Interactions. In: Monika Grejniec, editor. Drug-induced nutritional deficiencies.1st ed. New York: Van Nostrand Reinhold; 1989:83-103. 25. Beerhorst K, Tan I, Krom M, Verschuure P, Aldenkamp A. Antiepileptic drugs and high prevalence of low bone mineral density in a group of in patients with chronic epilepsy. ActaNeurolScand 2013; 128:273-80. 26. Shen C, Chen F, Zhang Y, Guo Y, Ding M. Association between useof antiepileptic drugs and fracture risk: A systematic review and meta-analysis. Bone 2014; 64: 246–53. 27. Perreault S, Dragomir A, Blais L, Moride Y, Rossignol M, Ste- Marie LG, et al. Population- based study of the effectiveness of bone- specific drugs inreducing the risk of osteoporotic fracture. Pharmacoepidemiol Drug Saf 2008; 17:248–59. 28. Ahmad BS, Hill KD, O’Brien TJ, Gorelik A, Habib N, Wark JD. Falls and fractures in patients chronically treated with antiepileptic drugs. Neurology 2012; 79:145-51. 29. Nicholas JM, Ridsdale L, Richardson MP, Grieve AP, Gulliford MC. Fracture risk with use of liver enzyme inducing antiepileptic drugs in people with active epilepsy: cohort study using the general practice research database. Seizure 2013; 22:37-42. 30. Beerhorst K, Schouwenaars F, Tan I, Aldenkamp A. Epilepsy: fractures and the role of cumulative antiepileptic drug load. Acta Neurolo Scand 2012; 125:54-9. 31. Weinstein RS, Bryce GF, Sappington LJ, King DW, Gallagher BB. Decreased Serum Ionized Calcium and Normal Vitamin D Metabolite Levels with Anticonvulsant Drug Treatment. J Clin Endocrinol Metab1984; 58:1003-9. 32. Fitzpatrick LA. Pathophysiology of bone loss in patients receiving anticonvulsant therapy. Epilepsy Behav 2004; 5:3-15. 33. Pack AM, Olarte LS, Morrell MJ, Flaster E, Resor SR, Shane E. Bone mineral density in an outpatient population receiving enzyme-inducing antiepileptic drugs. Epilepsy Behav 2003; 4:169-74. 34. Phabphal K, Geater A, Limapichat K, Sathirapanya P, Setthawatcharawanich S, Leelawattana R. Effect of switching hepatic enzyme- inducer antiepileptic drug to levetiracetam on bone mineral density, 25 hydroxy vitamin D, and parathyroid hormone in young adult patients with epilepsy. Epilepsia 2013; 54:e94-e8. 35. Richens A, Rowe D. Disturbance of calcium metabolism by anticonvulsant drugs. BMJ 1970; 4:73-76. 36. Hahn TJ, Hendin BA, Scharp CR, Haddad Jr JG. Effect of chronic anticonvulsant therapy on serum 25-hydroxycalciferol levels in adults. N Engl J Med 1972; 287:900-4. 37. Bouillon R, Reynaert J, Claes JH, Lissens W, De Moor P. The effect of anticonvulsant therapy on serum levels of 25-hydroxy-vitamin D, calcium, and parathyroid hormone. Clin Endocrinol Metab 1975; 41:1130-5 38. Lifshitz F, Maclaren NK. Vitamin D-dependent rickets in institutionalized, mentally retarded children receiving long-term anticonvulsant therapy .I.A survey of 288 patients. J Pediatr 1973; 83:612-20. 39. Deb S, Cowie VA, Tsanaclis LM, Richens A. Calcium homeostasis in mentally handicapped epileptic patients. J Intellectual Disabil Res 1985; 29:403-10. 40. Teagarden DL, Meador KJ, Loring DW. Low vitamin D levels are common in patients with epilepsy. Epilepsy res 2014; 108:1352-6. 41. Petty SJ,O’brien T, Wark J. Anti-epileptic medication and bone health. Osteoporis Int 2007; 18:129-42. 42. Wu FJ, Sheu SY, Lin HC. Osteoporosis is associated with antiepileptic drugs: a population- based study. Epileptic Disord 2014; 16:333-42. 43. Lazzari AA, Dussault PM, Thakore- James M, Gagnon D, Baker E, Davis SA, et al. Prevention of bone loss and vertebral fractures in patients with chronic epilepsy-Antiepileptic drug and osteoporosis prevention trial. Epilepsia 2013; 54:1997-2004. 44. Christiansen C, Rødbro P, Lund M. Incidence of anticonvulsant osteomalacia and effect of vitamin D: controlled therapeutic trial. BMJ 1973; 4:695-701. 45. Krause K, Bonjour J, Berlit P, Kynast G, Schmidt-Gayk H, Schellenberg B. Effect of long-term treatment with antiepileptic drugs on the vitamin status. Drug Nutr Interact 1987; 5:317-43. 46. Schwaninger M, Ringleb P, Winter R, Kohl B, Fiehn W, Rieser PA, et al. Elevated plasma concentrations of homocysteine in antiepileptic drug treatment. Epilepsia 1999; 40:345-50. 47. Apeland T, Mansoor MA, Strandjord RE, Kristensen O. Homocysteine concentrations and methionine loading in patients on antiepileptic drugs. Acta Neurol Scand 2000; 101:217-23. 48. Apeland T, Mansoor MA, Strandjord RE, Vefring H, Kristensen O. Folate, homocysteine and methionine loading inpatients on carbamazepine. Acta neurol scand 2001; 103:294-9. 49. Apeland T, Mansoor MA, Strandjord RE. Antiepileptic drugs as independent predictors of plasma total homocysteine levels. Epilepsy Res 2001; 47:27-35. 50. Apeland T, Mansoor MA, Pentieva K, McNulty H, Seljeflot I, Strandjord RE. The effect of B-vitamins on hyperhomocysteinemia in patients on antiepileptic drugs. Epilepsy Res 2002; 51:237-47. 51. Linnebank M, Moskau S, Semmler A, Widman G, Stoffel- Wagner B, Weller M, et al. Antiepileptic drugs interact with folate and vitamin B12 serum levels. Ann Neurol 2011; 69:352-9. 52. Scheinfeld N. Phenytoin in cutaneous medicine: Its uses and side effects. Dermatol Online J 2003; 9:6-22. 53. Reynolds E, Chanarin I, Milner G, Matthews D. Anticonvulsant therapy, folic acid and vitamin B12 metabolism and mental symptoms. Epilepsia 1966; 7:261-70. 54. Krause K-H, Kochen W, Berlit P, Bonjour J-P. Excretion of organic acids associated with biotin deficiency in chronic anticonvulsant therapy. Int J Vitam Nutr Res 1984; 54:217-22. 55. .Mock DM, Mock NI, Nelson RP, Lombard KA. Disturbances in biotin metabolism in children undergoing long-term anticonvulsant therapy. J Pediatr Gastroenterol Nutr 1998; 26:245-50. 56. Krause KH, Berlit P, Bonjour JP. Imparied biotin status in anticonvulsant therapy. Ann Neurol 1982; 12:485-6. 57. Mock DM, Dyken ME. Biotin catabolism is accelerated in adults receiving long-term therapy with anticonvulsants. Neurology 1997; 49:1444-7. 58. Gillman MA, Sandyk R. Nicotinic acid deficiency induced by sodium valproate. S Afr Med J 1984; 65:986. 59. Semmler A, Moskau-Hartmann S, Stoffel-Wagner B, Elger C, Linnebank M. Homocysteine plasma levels in patients treated with antiepileptic drugs depend on folate and vitamin B12 serum levels, but not on genetic variants of homocysteine metabolism. Clin Chem Lab Med 2013; 51:665-9. 60. Ray K. Epilepsy: Antiepileptic drugs reduce vitamin B12 and folate levels. Nature Rev Neurol 2011; 7:125. 61. Hoffbrand A, Necheles T. Mechanism of folate deficiency in patients receiving phenytoin. The Lancet 1968; 292:528-30. 62. Zahn C. Neurologic care of pregnant women with epilepsy. Epilepsia. 1998;39:S26-S31. 63. Belcastro V, Striano P. Antiepileptic drugs, hyperhomocysteinemia and B-vitamins supplementation in patients with epilepsy. Epilepsy res 2012; 102:1-7. 64. Bochyńska A, Lipczyńska-Łojkowska W, Gugała-Iwaniuk M, Lechowicz W, Restel M, Graban A, et al. The effect of vitamin B supplementation on homocysteine metabolism and clinical state of patients withchronic epilepsy treated with carbamazepine and valproic acid. Seizure 2012; 21:276-81. 65. Bailey LB. Folate in health and disease: in: Taylor and Francis group, editor. folate and neurological disease. 2nd ed. CRC Press; 2009; 325-355. 66. Paknahad Z, Chitsaz A, Zadeh AH, Sheklabadi E. Effects of common anti-epileptic drugs on the serum levels of homocysteine and folic acid. Int J Prev Med 2012; 3:S186–S190. 67. Jeeja MC, Jayakrishnan T, Narayanan PV, Kumar MSV, Thejus T, Anilakumari VP. Folic acid supplementation on homocysteine levels in children taking antiepileptic drugs: A randomized controlled trial. J PharmacolPharmacother 2014; 5:93-99. 68. Coburn SP. Location and turnover of vitamin B6 pools and vitamin B6 requirements of Humansa. Ann N Y AcadSci 1990; 585:76–85. 69. Kretsch MJ, Sauberlich HE, Newbrun E. Electroencephalographic changes and periodontal status during short-term vitamin B-6 depletion of young, nonpregnant women. Am J ClinNutr 1991; 53:1266-74. 70. Attilakos A, Papakonstantinou E, Schulpis K, Voudris K, Katsarou E, Mastroyianni S, et al. Early effect of sodium valproate and carbamazepine monotherapy on homocysteine metabolism in children with epilepsy. Epilepsy Res 2006; 71:229-32. 71. Apeland T, Froyland ES, Kristensen O, Strandjord RE, Mansoor MA. Drug-induced pertubation of the aminothiol redox-status in patients with epilepsy: improvement by B-vitamins. Epilepsy Res 2008; 82:1-6. 72. Sawicka-Glazer E, Czuczwar SJ. Vitamin C: A new auxiliary treatment of epilepsy? Pharmacol Rep 2014; 66: 529–533. 73. Ullah I, Badshah H, Naseer MI, Lee HY, Kim MO. Thymoquinone and Vitamin C Attenuates Pentylenetetrazole-Induced Seizures Via Activation of GABAB1 Receptor in Adult Rats Cortex and Hippocampus. Neuromolecular Med2014; 17:1-12. 74. Dubick MA, Keen CL. Alterations in tissue trace element and ascorbic acid metabolism in phenytoin-fed rats and mice. J Nutr1985; 115:1481-7. 75. Wilcox RE, Riffee WH, Goldman C-PL, Young RK. Effects of ascorbate on a dopaminergic response: Apomorphine-induced modification of pentylenetetrazol induced seizures in mice. Psychopharmacology 1984; 83:48-50. 76. Fex G, Larsson K, Andersson A, Berggren-Söderlund M. Low serum concentrationof all-trans and 13-cis retinoic acids in patients treated with phenytoin, carbamazepine and valproate. Arch Toxicol 1995; 69:572-4. 77. Leo MA, Lowe N, Lieber CS. Decreased hepatic vitamin A after drug administration in men and in rats. Am J Clin Nutr 1984; 40:1131-6. 78. Cornelissen M, Steegers-Theunissen R, Kollée L, Eskes T, Vogels-Mentink G, Motohara K, et al. Increased incidence of neonatal vitamin K deficiency resulting from maternal anticonvulsant therapy. Am J Obstet Gynecol 1993; 168:923-8. 79. Cornelissen M, Steegers-Theunissen R, Kollee L, Eskes T, Motohara K, Monnens L. Supplementation of vitamin K in pregnant women receiving anticonvulsant therapy prevents neonatal vitamin K deficiency. Am J Obstet Gynecol1993; 168:884-8. 80. Nazıroğlu M, Yürekli VA. Effects of antiepileptic drugs on antioxidant and oxidant molecular pathways: focus on trace elements. Cell Mol Neurobiol 2013; 33:589-99. 81. Hurd R, Van Rinsvelt H, Wilder B, Karas B, Maenhaut W, De Reu L. Selenium, zinc, and copper changes with valproic acid Possible relation to drug side effects. Neurology 1984; 34:1393-95. 82. Palm R, Hallmans G. Zinc and copper metabolism in phenytoin therapy. Epilepsia 1982; 23:453-61. 83. Lewis-Jones M, Evans S, Culshaw M. Cutaneous manifestations of zinc deficiency during treatment with anticonvulsants. BMJ (Clinical research ed) 1985; 290:603-604. 84. Kuzuya T, Hasegawa T, Shimizu K, Nabeshima T. Effect of anti-epileptic drugs on serum zinc and copper concentrations in epileptic patients. Int J Clin Pharmacol Ther Toxicol 1993; 31:61-5. 85. Liu C-S, Wu H-M, Kao S-H, Wei Y-H. Serum trace elements, glutathione, copper/zinc superoxide dismutase, and lipid peroxidation in epileptic patients with phenytoin or carbamazepine monotherapy. Clin Neuropharmacol 1998; 21:62-4. 86. Castro-Gago M, Pérez-Gay L, Gómez-Lado C, Castiñeiras-Ramos DE, Otero-Martínez S, Rodríguez-Segade S. The influence of valproic acid and carbamazepine treatment on serum biotin and zinc levels and on biotinidase activity. J Child Neurol 2011; 26:1522-4. 87. Yuen W, Whiteoak R, Thompson R. Zinc concentrations in leucocytes of patients receiving antiepileptic drugs. J Clin Pathol 1988; 41:553-5. 88. Ghose K, Taylor A. Hypercupraemia induced by antiepileptic drugs. Hum Exp Toxicol 1983; 2:519-29. 89. Morris DR, Levenson CW. Ion channels and zinc: mechanisms of neurotoxicity and neurodegeneration. J Toxicol 2012; 201:1-6. 90. Gower- Winter SD, Levenson CW. Zinc in the central nervous system: from molecules to behavior. Biofactors 2012; 38:186-93. 91. Yorulmaz H, Şeker FB, Demir G, Yalçın İE, Öztaş B. The Effects of Zinc Treatment on the Blood–Brain Barrier Permeability and Brain Element Levels During Convulsions. Biol Trace Elem Res 2013; 151:256-62. 92. Wojciak RW, Mojs E, Stanislawska-Kubiak M, Samborski W. The serum zinc, copper, iron, and chromium concentrations in epileptic children. Epilepsy Res 2013; 104:40-4. 93. Kessler SK, Gallagher PR, Shellhaas RA, Clancy RR, Bergqvist A. Early EEG improvementafter ketogenic diet initiation. Epilepsy Res 2011; 94:94-101. 94. Wilder R, editor. The effects of ketonemia on the course of epilepsy. Mayo Clin Proc 1921; 2: 307-308. 95. Lefevre F, Aronson N. Ketogenic diet for the treatment of refractory epilepsy in children: a systematic review of efficacy. Pediatrics 2000; 105:46-53. 96. Freeman JM, Kossoff EH, Hartman AL. The ketogenic diet: one decade later. Pediatrics 2007; 119:535-43. 97. Danial NN, Hartman AL, Stafstrom CE, Thio LL. How does the ketogenic diet work? Four potential mechanisms. J Child Neurol 2013; 28:1027-33. 98. Klepper J. GLUT1 deficiency syndrome in clinical practice. Epilepsy res 2012; 100:272-7. 99. Neal EG, Chaffe H, Schwartz RH, Lawson MS, Edwards N, FitzsimmonsG, et al. The ketogenic diet for the treatment of childhood epilepsy: a randomised controlled trial. Lancet Neurol 2008; 7:500-6. 100.Lutas A, Yellen G. The ketogenic diet: metabolic influences on brain excitability and epilepsy. Trends Neurosci 2013; 36:32-40. 101.Hartman AL, Gasior M, Vining EP, Rogawski MA. The neuropharmacology of the ketogenic diet. Pediatr Neurol 2007; 36:281-92. 102.Stafstrom CE, Rho JM. The ketogenic diet as a treatment paradigm for diverse neurological disorders. Front Pharmacol 2012; 3:1-8. 103.Yoon J-R, Lee EJ, Kim HD, Lee JH, Kang H-C. Polyunsaturated fatty acid-enriched diet therapy for a child with epilepsy. Brain Dev 2014; 36:163-6. 104.Huttenlocher PR. Ketonemia and seizures: metabolic and anticonvulsant effects of two ketogenic diets in childhood epilepsy. Pediatr Res 1976; 10:536-40. 105.Owen O, Morgan A, Kemp H, Sullivan J, Herrera M, Cahill Jr G. Brain metabolism during fasting. J Clin Invest 1967; 46:1589-95. 106.Smith AL, Satterthwaite HS, Sokoloff L. Induction of Brain D (m)-β-Hydroxybutyrate Dehydrogenase Activity by Fasting. Science 1969; 163:79-81. 107.Vining EP. Clinical efficacy of the ketogenic diet. Epilepsy Res 1999; 37:181-90. 108.YmC L, Wang H. Medium-chain triglyceride ketogenic diet, an effective treatment for drug-resistant epilepsy and a comparison with other ketogenic diets. Biomed J2013;36:9-15. 109.Huttenlocher P, Wilbourn A, SignoreJ. Medium- chain triglycerides as a therapy for intractable childhood epilepsy. Neurology 1971; 21:1526-632. 110. Bach AC, Babayan VK. Medium-chain triglycerides: an update. Am J Clin Nutr 1982; 36:950-62. 111. Wlaź P, Socała K, Nieoczym D, Żarnowski T, Żarnowska I, Czuczwar SJ, et al. Acute anticonvulsant effects of capric acid in seizure tests in mice. Prog Neuropsychopharmacol Biol Psychiatry 2015; 57:110-6. 112. Chang P, Zuckermann AM, Williams S, Close AJ, Cano- Jaimez M, McEvoy JP, et al. Seizure control by derivatives of medium chain fatty acids associated with the ketogenic diet show novel branching-point structure for enhanced potency. J Pharmacol Exp Ther 2015; 352:43-52. 113. Henderson ST. Ketone bodies as a therapeutic for Alzheimer’s disease. Neurotherapeutics 2008; 5:470-80. 114. Johnson RC, Young SK, Cotter R, Lin L, Rowe W. Medium-chain-triglyceride lipid emulsion: metabolism and tissue distribution. Am J Clin Nutr 1990; 52:502-8. 115. McGarry JD, Foster DW. The Regulation of Ketogenesis from Octanoic Acid The Role Of The Tricarboxylic Acid Cycle And Fatty Acid Synthesis. J Biol Chem 1971;246:1149-59. 116. Papamandjaris AA, MacDougall DE, Jones PJ. Medium chain fatty acid metabolism and energy expenditure: obesity treatment implications. Life Sci 1998; 62:1203-15. 117. Samson Jr FE, Dahl N, Dahl DR. A study on the narcotic action of theshort chain fatty acids. J Clin Invest 1956;35:1291-8. 118. Ebert D, Haller RG, Walton ME. Energy contribution of octanoate to intact rat brain metabolism measured by 13C nuclear magnetic resonance spectroscopy. J Neurosci 2003; 23:5928-35. 119. Edmond J, Higa TA, Korsak RA, Bergner E, Lee WNP. Fatty acid transport and utilization for the developing brain. J Neurochem 1998; 70:1227-34. 120.Rapoport SI. In vivo fatty acid incorporation into brain phosholipids in relation to plasma availability, signal transduction and membrane remodeling. J Mol Neurosci 2001; 16:243-61. 121.Spector R. Fatty Acid Transport Through the Blood- Brain Barrier. J Neurochem 1988; 50:639-43. 122.Walker C, McCandless D, McGarry J, Schenker S. Cerebral energy metabolism in short-chain fatty acidinduced coma. J Lab Clin Med 1970; 76:569-83. 123.Hughes SD, Kanabus M, Anderson G, Hargreaves IP, Rutherford T, Donnell MO, et al. The ketogenic diet component decanoic acid increases mitochondrial citrate synthase and complex I activity in neuronal cells. J Neurochem 2014; 129:426-33. 124.Kamata Y, Shiraga H, Tai A, Kawamoto Y, GohdaE. Induction of neurite outgrowth in PC12 cells by the medium-chain fatty acid octanoic acid. Neuroscience 2007; 146:1073-81. 125.Jiang W, Van Cleemput J, Sheerin AH, Ji SP, Zhang Y, Saucier DM, et al. Involvement of extracellular regulated kinase and p38 kinase in hippocampal seizure tolerance. J Neurosci Res 2005; 81:581-8. 126.Jung S, Bullis JB, Lau IH, Jones TD, Warner LN, Poolos NP. Downregulation of dendritic HCN channel gating in epilepsy is mediated by altered phosphorylation signaling. J Neurosci 2010; 30:6678-88. 127.Scheffer IE. Genetics of the epilepsies: channelopathies and beyond. Epilepsia.2011;52:192-3. 128.Genton P. When antiepileptic drugs aggravate epilepsy. Brain Dev 2000; 22:75-80. 129.Dressler A, Trimmel-Schwahofer P, Reithofer E, Mühlebner A, Gröppel G, Reiter-Fink E, et al. Efficacy and tolerability of the ketogenic diet in Dravet syndrome- Comparison with various standard antiepileptic drug regimen. Epilepsy Res 2015; 109:81-9. 130.Dahlin M, Hjelte L, Nilsson S, Åmark P. Plasma phospholipid fatty acids are influenced by a ketogenic diet enriched with n-3 fatty acids in children with epilepsy. Epilepsy Res 2007; 73:199-207. 131.DeGiorgio CM, MillerPR, Harper R, Gornbein J, Schrader L, Soss J, et al. Fish oil (n-3 fatty acids) in drug resistant epilepsy: a randomised placebo-controlled crossover study. J Neurol Neurosurg Psychiatry 2015; 86:670-5. 132.Taha AY, Burnham WM, AuvinS. Polyunsaturated fatty acids and epilepsy. Epilepsia 2010; 51:1348-58. 133.Taha A, Ryan MAA, Cunnane SC. Despite transient ketosis, the classic high-fat ketogenic diet induces marked changes in fatty acid metabolism in rats. Metabolism 2005; 54:1127-32. 134.Bough KJ, Rho JM. Anticonvulsant mechanisms of the ketogenic diet. Epilepsia 2007; 48:43-58. 135.Bough KJ, Wetherington J, Hassel B, Pare JF, Gawryluk JW, Greene JG, et al. Mitochondrial biogenesis in the anticonvulsant mechanism of theketogenic diet. Ann Neurol 2006; 60:223-35. 136.Kossoff EH, Zupec- Kania BA, Amark PE, Ballaban- Gil KR, Christina Bergqvist A, Blackford R, et al. Optimal clinical management of children receiving the ketogenic diet: recommendations of the International Ketogenic Diet Study Group. Epilepsia 2009; 50:304-17. 137.Bergqvist A, Schall JI, Stallings VA. Vitamin D status in children with intractable epilepsy, and impact of the ketogenic diet. Epilepsia 2007; 48:66-71. 138.Sharma S, Jain P. The ketogenic diet and other dietary treatments for refractory epilepsy in children. Ann Indian Acad Neurol 2014; 17:253-8. 139.Kim JT, Kang H-C, Song J-E, Lee MJ, Lee YJ, Lee EJ, et al. Catch-up growth after long-term implementation and weaning from ketogenic diet in pediatric epileptic patients. Clin Nutr 2013; 32:98-103. 140.Mosek A, Natour H, Neufeld MY, Shiff Y, Vaisman N. Ketogenic diet treatment in adults with refractory epilepsy: a prospective pilot study. Seizure 2009; 18:30-3. 141.Klein P, Janousek J, Barber A, Weissberger R. Ketogenic diet treatment in adults with refractory epilepsy. Epilepsy Behav 2010; 19:575-9. 142.Berry- Kravis E, Booth G, Sanchez AC, Woodbury- Kolb J. Carnitine levels and theketogenic diet. Epilepsia 2001; 42:1445-51. 143.Schwartz RH, Eaton J, Bower B, Aynsley- Green A. Ketogenic Diets In The Treatment Of Epilepsy: Short-Term Clinical Effects. Dev Med Child Neurol 1989; 31:145-51. 144.Chesney D, Brouhard BH, Wyllie E, Powaski K. Biochemical abnormalities of the ketogenic diet in children. Clin Pediatr 1999; 38:107-9. 145.Kang HC, Chung DE, Kim DW, Kim HD. Early- and late onset complications of the ketogenic diet for intractable epilepsy. Epilepsia 2004; 45:1116-23. 146.Wheless JW. The ketogenic diet: an effective medical therapy with side effects. J Child Neurol 2001; 16:633-5. 147.Fraser D, Whiting S, Andrew R, Macdonald E, Musa– Veloso K, Cunnane S. Elevated polyunsaturated fatty acids in blood serum obtained from children on the ketogenic diet. Neurology 2003; 60:1026-9. 148.Freeman J, Veggiotti P, Lanzi G, Tagliabue A, Perucca E. The ketogenic diet: from molecular mechanisms to clinical effects. Epilepsy Res 2006; 68:145-80. 149.Lin Q, Ruuska SE, Shaw NS, Dong D, Noy N. Ligand selectivity of the peroxisome proliferator-activated receptor α. Biochemistry 1999; 38:185-90. 150.Nei M, Ngo L, Sirven JI, Sperling MR. Ketogenic diet in adolescents and adults with epilepsy. Seizure 2014;23:439-442. 151.Schoeler NE, Wood S, Aldridge V, Sander JW, Cross JH, Sisodiya SM. Ketogenic dietary therapies for adults with epilepsy: Feasibility and classification of response. Epilepsy Behav 2014; 37:77-81. 152.Kossoff EH, McGrogan JR, Bluml RM, Pillas DJ, Rubenstein JE, Vining EP. A modified Atkins diet is effective for the treatment of intractable pediatric epilepsy. Epilepsia 2006; 47:421-4. 153.Pfeifer HH, Thiele EA. Low-glycemic-index treatment: a liberalized ketogenicdiet for treatment of intractable epilepsy. Neurology 2005; 65:1810-2. 154.Coppola G, D’Aniello A, Messana T, Di Pasquale F, della Corte R, Pascotto A, et al. Low glycemic index diet in children and young adults with refractory epilepsy: first Italian experience. Seizure 2011; 20:526-8. 155.Kossoff EH, Turner Z, Bluml RM, Pyzik PL, Vining EP. A randomized, crossover comparison of daily carbohydrate limits using the modified Atkins diet. Epilepsy Behav 2007; 10:432-6. 156.Kossoff EH, Dorward JL. The modified Atkins diet. Epilepsia 2008; 49:37-41. 157.Sharma S, Sankhyan N, Gulati S, Agarwala A. Use of the modified Atkins diet in infantile spasms refractory to firstline treatment. Seizure 2012; 21:45-8. 158.Sharma S, Sankhyan N, Gulati S, Agarwala A. Use of the modified Atkins diet for treatment of refractory childhood epilepsy: a randomized controlled trial. Epilepsia 2013; 54:481-6. 159.Karimzadeh P, Sedighi M, Beheshti M, Azargashb E, Ghofrani M, Abdollahe-Gorgi F. Low Glycemic Index Treatment in pediatric refractory epilepsy: The first Middle East report. Seizure 2014; 23:570-2.